Kritik Nalar Al-Jabiri dan Implikasinya Terhadap Perkembangan Ekonomi Syariah Modern: Perspektif Trilogi Epistemologi untuk Kemajuan Islam - Fadhil Wafa; Abid Rohmanu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Modern Islamic philosopher and commentator Muhammad Abid Al-Jabiri helped advance the study of Quranic interpretation today. His critical thinking of Arabic reason made him famous among academics. Abid Al Jabiri's